Three Dimensional Osteometric Analysis of Mandibular Symmetry and Morphological Consistency in Cats - Southerden, Peter; Haydock, Richard M.; Barnes, Duncan M. (Frontiers in Veterinary Science, 2018)
Objectives. The aim of this study was to describe a number of anatomical reference points which can be used to measure mandibular morphology and assess the degree of mandibular symmetry in a group of normal cats. Comparisons were then made between cats to evaluate correlations between morphological measurements and degree of inter-cat variation. This will provide data valuable evaluating and developing techniques for caudal mandibular fracture repair. Methods. Twenty-seven mixed breed cats (26 Domestic Shorthaired and 1 Domestic Longhaired) with no history of head trauma, intact undamaged mandibles, both mandibular fourth premolars and first molars present which had a full skull CT scan were included in this study. Anatomical reference points were defined on maximum intensity projections of multiplanar reconstruction of the mandibles and measurements taken. The ratios between paired right and left measurements, and the ratio of jaw widths at the coronoid process and mandibular foramen were calculated. All analyses were performed using R version 3.3.3 and the multcomp library. Results. None of the right:left ratios were detected as being significantly different from 1 and the coefficient of variation values were all very small showing that when cats deviate from the mean ratio they do so by only a small amount. Measurements analysed to determine how consistent individual measurements were between cats showed that the most consistent measurement was the lateral ramus inclination angle. The least consistent measurements were ramus height and jaw width at the mental foramen. The correlation between pairs of measurements of the right and left ramus was analysed and demonstrated a strong correlation between the height, width and length of the ramus. Conclusions. This study has demonstrated a low level of asymmetry between contralateral mandibles in cats, a high level of consistency in the dimensions of mandibles between cats and a strong correlation between the height, width and length of the ramus.